The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0972150918789986
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Volatility Spillover between Stock Market and Foreign Exchange Market: Instances from Indian Market from Pre-, during and Post- Subprime Crisis Periods

Abstract: Modern businesses are so inter-twined that a cause in one market affects other markets throughout the Globe. The 2008 subprime crisis is one of such evidences of inter-linkage of global markets. Such type of event motivates many studies to analyse the transmission of volatility from one market to another market. The study aims to analyse the volatility spillover effect between CNX Nifty and exchange rates covering for three different currencies, that is, USD, GBP and yen. GARCH (1,1) and EGARCH (1,1) have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In contrast to Dahir et al (2018), they find unidirectional spillover effects from the exchange rates to stock returns in the short-run for all BRICS and shocks to the US S&P 500 influence all BRICS stock markets except India. The results are similar to those of Bal, Manglani and Deo (2018), who used the GARCH and EGARCH and found a unidirectional effect from the exchange rate market to the stock market for India. Using Markov-switching (MS) VAR models, Chkili and Nguyen (2014)…”
Section: Literature Reviewsupporting
confidence: 86%
“…In contrast to Dahir et al (2018), they find unidirectional spillover effects from the exchange rates to stock returns in the short-run for all BRICS and shocks to the US S&P 500 influence all BRICS stock markets except India. The results are similar to those of Bal, Manglani and Deo (2018), who used the GARCH and EGARCH and found a unidirectional effect from the exchange rate market to the stock market for India. Using Markov-switching (MS) VAR models, Chkili and Nguyen (2014)…”
Section: Literature Reviewsupporting
confidence: 86%
“…Furthermore, this study also found significant return and volatility spillover indices in Australia, Singapore, the United States and the United Kingdom during both Asian crisis and global financial crisis. Apart from this, many studies (e.g., Bae & Zhang, 2015; Bal, Manglani, & Deo, 2018; Kang & Yoon, 2011; Karunanayake, Valadkhani, & O’Brien, 2010; Li & Giles, 2015) found significant integration among different financial markets in the post global financial crisis period.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Hung (2018) and Zabiulla (2015) used this model to examine the volatility spillover in foreign exchange markets. Habiba, Peilong, Hamid, and Shahzad (2019), Bal, Manglani, and Deo (2018) and Majumder and Nag (2018) used EGARCH model in their studies to capture the asymmetric volatility spillover between stock markets.…”
Section: Review Of Literaturementioning
confidence: 99%